Training on Preparation of Financial Reports Based on Accurate Application and Tax Calculation for UMKM in Mendalo Darat Village, Jambi Luar Kota District, Muaro Jambi Regency - Safelia, Nela; Afrizal; Tiswiyanti, Wiwik; Olimsar, Fredy; Putra, Dios Nugraha (Indonesian Journal of Society Development, 2024)
This training and financial report preparation are designed as a form of community service with the aim of enhancing their knowledge and skills in preparing financial reports and accurate application-based tax calculations for MSME entrepreneurs in Mendalo Darat Village, Muaro Jambi Regency. Through this training, participants are expected to understand the importance of preparing good and correct financial reports in accordance with accounting standards, as well as to increase awareness of the tax obligations that entrepreneurs must fulfill. The results of this activity show that the participants' understanding of basic accounting concepts, tax calculations, and the use of the Accurate application has significantly improved. Participants are able to apply the new knowledge, starting from entering transaction data to producing complete financial reports. In addition, they also showed an increased awareness of tax obligations and how to correctly calculate taxes according to the applicable regulations. This training has a positive impact on the financial management of MSMEs, which is expected to help improve operational efficiency and business sustainability